Petrography and geochemistry of sandstones succession of the Qal'eh Dokhtar Formation (Middle-Upper Jurassic), east central Iran: Implications for provenance, tectonic setting and palaeoweathering. (November 2018) - Sabbagh Bajestani, Mahnaz; Mahboubi, Asadollah; Moussavi-Harami, Reza; Nadjafi, Mehdi
Abstract: Sandstones of the Qal'eh Dokhtar Formation west of Boshrouyeh, Central Iran, were analyzed for Petrographic and geochemical (major and selected trace elements) to infer their provenance, intensity of palaeoweathering of the source rocks and tectonic setting. This formation is composed mainly of alternating marine sandstones, laminated greenish to light gray shales with well bedded gray limestones. Texturally, these sandstones are fine grained, subangular to subrounded and moderately to well sorted. Based on the petrographic study, modal analysis and geochemical data, they can be classified as quartzarenites and sublitharenites. The provenance and tectonic setting of theses sandstones have been assessed using integrated petrographic and geochemical studies. Petrographic data suggest that the sediments were derived from plutonic rocks. Petrographic analysis reveals recycled origin and craton interior setting were the dominate source. The geochemical investigations are recommended that these rocks were originated from quartzose sedimentary source. Chemically, major and trace element concentrations in the sandstones indicate deposition in a passive continental margin setting. Average CIA, CIW and PIA values (69%, 75%, and 72%, respectively) imply moderately to high degree of chemical weathering, which may reflect humid climate condition in the source area. The petrographic analysis, geochemical data and palaeogeographical models confirm that the Qal'eh Dokhtar Formation sandstones generally consequent from mature recycled continental sedimentary rocks and deposited on the passive margin alongshore setting of the Neotethys Ocean. Highlights: Modal analysis (QmFLt) show the sandstones of Qal'eh Dokhtar Fm. located in the recycled origin and craton interior field. The geochemical characteristics suggest the passive margin setting for these sandstones. The CIA, CIW and PIA values are indicative of moderately to comparatively high weathering in the source area.